2011
DOI: 10.1016/j.athoracsur.2010.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Existing General Population Models Inaccurately Predict Lung Cancer Risk in Patients Referred for Surgical Evaluation

Abstract: Background atients undergoing resections for suspicious pulmonary lesions have a 9-55% benign rate. Validated prediction models exist to estimate the probability of malignancy in a general population and current practice guidelines recommend their use. We evaluated these models in a surgical population to determine the accuracy of existing models to predict benign or malignant disease. Methods We conducted a retrospective review of our thoracic surgery quality improvement database (2005-2008) to identify pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 19 publications
3
35
0
1
Order By: Relevance
“…( Tables S5, S6 ). [33][34][35] Another used data from the PLCO (Prostate, Lung, Colorectal, Ovarian Cancer Screening Trial) of lung cancer screening with chest radiography and found that although a lung mass (not surprisingly) was highly predictive of malignancy (OR, 11.2; 95% CI, 6.3-19.9), the fi nding of a lung nodule was not (OR, 1.4; 95% CI, 0.8-2.5). 36 The most extensively validated model was developed by investigators at the Mayo Clinic who used multiple logistic regression analysis to identify six independent predictors of malignancy in 419 patients with noncalcifi ed nodules that measured between 4 and 30 mm in diameter on chest radiography.…”
Section: Clinical Probability Of Cancermentioning
confidence: 99%
“…( Tables S5, S6 ). [33][34][35] Another used data from the PLCO (Prostate, Lung, Colorectal, Ovarian Cancer Screening Trial) of lung cancer screening with chest radiography and found that although a lung mass (not surprisingly) was highly predictive of malignancy (OR, 11.2; 95% CI, 6.3-19.9), the fi nding of a lung nodule was not (OR, 1.4; 95% CI, 0.8-2.5). 36 The most extensively validated model was developed by investigators at the Mayo Clinic who used multiple logistic regression analysis to identify six independent predictors of malignancy in 419 patients with noncalcifi ed nodules that measured between 4 and 30 mm in diameter on chest radiography.…”
Section: Clinical Probability Of Cancermentioning
confidence: 99%
“…For those who are more quantitatively inclined, clinical prediction models (or risk assessment models) have been developed to provide a more explicit, transparent, and reproducible assessment of this risk. One commonly cited model was developed and internally validated at the Mayo Clinic (4) and subsequently validated in independent samples of U.S. veterans with lung nodules, a surgical population from an academic center in the southeastern United States, and patients from the Netherlands who underwent positron emission tomography (5)(6)(7). A similar model was developed and validated using samples of U.S. veterans with a higher prevalence of malignancy (8).…”
mentioning
confidence: 99%
“…The adoption of this latter strategy, defined on the basis of risk of malignancy, young age, patient preference (as in anxious subjects), may be better justified, keeping in mind the ALARA principle, choosing a segmental scan with respect to an unjustified whole body PET/CT. On the other hand, the advantage of a surveillance strategy, for 4 years, has to be weighed against the disadvantage of delaying diagnosis of malignant nodules [7], the incidence of which is reported up to 62 % in patients with higher likelihood of benign disease [27].…”
Section: Radiation Dosimetry and Cancer Riskmentioning
confidence: 99%